Addressing global challenges: Royal Geographical Society (with IBG) Medals and Awards ceremony 2016. Issue 3 (September 2016) - Crane, Nicholas; Geldof, Bob; Martin, Ron; Raghuram, Parvati; Sharp, Jo; Storper, Michael
Abstract : The Royal Geographical Society (with IBG)'s annual Medals and Awards recognise achievements in researching, communicating and teaching a wide range of geographical knowledge. The speeches and citations are a record of the 2016 ceremony, with contributions by Bob Geldof KBE, and Professors Ron Martin, Parvati Raghuram, Jo Sharp and Michael Storper. The speeches include comments on the importance of geography for understanding and tackling global challenges, engaging wider publics, geographical imagination, collaboration, fieldwork, travel and education.